A Compositional Semantics for the Reversible p-Calculus - Cristescu, Ioana; Krivine, Jean; Varacca, Daniele (2013 28th Annual ACM/IEEE Symposium on Logic in Computer Science, 2013)
We introduce a labelled transition semantics for the reversible π-calculus. It is the first account of a compositional definition of a reversible calculus, that has both concurrency primitives and name mobility. The notion of reversibility is strictly linked to the notion of causality. We discuss the notion of causality induced by our calculus, and we compare it with the existing notions in the literature, in particular for what concerns the syntactic feature of scope extrusion, typical of the π-calculus.